THE STRUCTURE OF CLASSROOM INTERACTION PRODUCED IN SENIOR HIGH SCHOOL ENGLISH CLASSES - Hamzah Hamzah (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
This paper discusses the structure of the interaction in pedagogical discourse produced by participants in English classes at senior high schools. The source of data consited of twenty lesson’s transcript regarded as complete interaction stating from opening to closing. The analysis was based on Sinclair and couldhard model looking interaction as a chierarchical units in which the higher level units consist of the lower level units. The findings reveals that the structure of the lesson consisted of opening, topic discussion and closing. The opening unit consisted of greeting and topic introduction and exchanges relating to motivating students and the introduction of the lesson outline were not found. The transactional units were not strategically wrapped, preliminary exchanges were usually availeble but the terminal exchanges were mostly absent. . It might lead to a believe that the teacher develop the transaction’s flow as if it were a face to face and personal interaction. The exchange units were dominated by eliciting moves showing the characteristics of traditional classroom where the teacher dominated the class. The move units were dominated by head acts and less than five percent elaborated with prehead acts or posthead acts and the selection act were not used by the teacher to enhanced the student’s learning. The closing units consisted of few summary and greeting. In conclusion the structure of the classrooom interaction studied are closer to tradional classroom as compared to thinking classroom. Key words: classroom discourse, interaction, structure of the interaction, teacher talk